Pemanfaatan Teknologi Satelit untuk Mitigasi Bencana dan Penguatan Resiliensi Nasional terhadap Ancaman Geospasial di Indonesia: Indonesia - Afriyanto, Mulya; Supriyadi, Asep Adang; Arief, Syachrul; Waluyo, Dangan (PendIPA Journal of Science Education, 2025)
Indonesia is one of the countries with the highest level of geospatial disaster risk due to its position on the Pacific Ring of Fire and its exposure to earthquakes, tsunamis, volcanic eruptions, floods, and landslides. The increasing complexity and frequency of disasters, exacerbated by climate change, demands a faster, more accurate, and integrated monitoring system. However, previous studies have focused more on the technical aspects of disaster monitoring without comprehensively examining the strategic role of satellite technology in strengthening Indonesia's national resilience. This gap is the basis for this study. This study aims to analyze the contribution of satellite technology in disaster mitigation and assess how satellite data integration can strengthen national resilience to geospatial threats. The method used is a systematic literature review of reputable international publications from 2014 to 2025 that discuss remote sensing technology, InSAR, damage mapping, early warning systems, and geospatial integration for disaster risk management. The results of the study show that satellite technology plays an important role in three main aspects: (1) real-time disaster monitoring through multisensor data capable of covering a wide area; (2) improving the accuracy of early warning systems for various geospatial disasters; and (3) strengthening national resilience through support for damage mapping, rapid response, strategic decision-making, and inter-agency coordination. The novelty of this research lies in the development of an integrative synthesis that links the use of satellite data with Indonesia's national resilience framework, as well as the affirmation of the need to integrate satellite technology into national disaster management policies. These findings have important implications for strengthening modern mitigation systems and adapting to the escalation of geospatial risks in the future.